An Interactive Web Application Helps Students Explore Water Balance Concepts - Gannon, John P.; McGuire, Kevin J. (Frontiers in Education, 2022)
The concept of a water balance is a foundational topic in hydrology classrooms. While understanding and applying this concept is crucial to the introduction of more advanced topics, students often struggle to develop a thorough understanding of the relationships between components, assumptions, and limitations of a water balance. To aid students in developing a working understanding of a water balance, we developed a web application that runs a one dimensional Thornthwaite-type water balance at any of thousands of NOAA climate stations across the continental United States using the local soil-water storage capacity at the station location. Within the app, students can manipulate the soil-water storage capacity, latitude, temperature, and precipitation to better understand how it works and explore scenarios of land use, extreme weather, and climate change. The application is free and will run on any device that can open an internet browser window (laptops, chromebooks, smartphones, etc). Here we present the details of the model, functionality of the application, and link to several ready-made classroom activities. Finally, results from student surveys in two hydrology classrooms show that students may learn water balance concepts more effectively than traditional methods such as spreadsheet computations.